(untitled) (Journal of Bangladesh Institute of Planners, 2010)
Socio-economic facilities play an important role in the development of regions and affect the maintenance and reinforcement of people’s activity. Similar with the common scenario of most of the districts in Bangladesh, the distribution of socio-economic facilities in Narsingdi district is concentrated disproportionately rather than to an equitable and uniform manner. A detailed analysis and investigation has been carried out to determine the regional imbalances in distribution pattern of some socio-economic facilities among different Upazilas of the study area using different statistical methods and Geographic Information Tools. This study also examines the concentration pattern of socio-economic facilities and examined some possible factors liable behind the concentration of those facilities in some particular Upazilas. Based on the outcome of the study, finally some policies and strategies have been provided for upgrading the distribution pattern of socioeconomic facilities. Journal of Bangladesh Institute of Planners, Vol. 3, Dec 2010, pp. 143-152